Distância potencial de deriva em aplicações por drone pulverizador no cultivo de milho - Carneiro, Maicon Leonardo Damaceno (2024)
In Brazil, corn (zea mays) is one of the most cultivated grains, due to the favorable climate and the increase in planted areas, in the harvest, off-season and third harvest, and its economic importance, which is characterized by different forms of use, mainly in animal feed, and also for its use in the food industry. Due to the need to produce each time Furthermore, over time, technologies were developed to maximize production, which will from seed technology, fertilization, planting, spraying, illnesses. Therefore, we sought to use technology, and as an example we have the use of drones, which has become of paramount importance and has grown every day. This is due to the advantages of its use, such as the possibility of entering the crop when soil conditions are not favorable conditions, and also avoiding crushing of the culture, since it can be used in the different phenological stages of the crop. In this context, the objective of this work was to evaluate the potential drift distance in spray drone applications in the cultivation of corn. The experiment was carried out in the experimental area of the Agronomy course at UTFPR, Pato Branco campus - PR. The DJI® brand drone, model Agras MG-1P, was used, which has four spray tips, spray width between 3 and 6 meters and capacity 10 liters of syrup in the tank. A randomized block design (DBC) was used, composed of five treatments, three volumes of spray (7.5, 15, 22.5 L ha-1) and two spray tips (XR11001 and TXA8001), with four replications, totaling 24 plots. To evaluate the potential drift distance, 3 water-sensitive papers were used, which were fixed in the upper, middle and lower thirds of the plants. Four plants of each installment, totaling 36 water-sensitive papers. To simulate the effect of different volumes of spray solution and spray tips at the drift distance of the generated drops, the computational program DRIFTSIM® v.1.12.04, the computational simulation allowed predicting the risk of drift under the operating conditions encountered during the experiment and with both chosen spray tips and the three spray volumes (7.5, 15, 22.5 L ha-1), with the droplet diameter and the type of spray tip used were factors that influenced to drift.